2020
DOI: 10.3390/ijms21041250
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Effects of Plant Polyphenols: Molecular Mechanisms

Abstract: The increasing extension in life expectancy of human beings in developed countries is accompanied by a progressively greater rate of degenerative diseases associated with lifestyle and aging, most of which are still waiting for effective, not merely symptomatic, therapies. Accordingly, at present, the recommendations aimed at reducing the prevalence of these conditions in the population are limited to a safer lifestyle including physical/mental exercise, a reduced caloric intake, and a proper diet in a convivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
245
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(250 citation statements)
references
References 294 publications
(337 reference statements)
1
245
0
4
Order By: Relevance
“…Vitagenes encode for the Hsps, HO-1 and sirtuin protein systems, whose activation is most likely dependent on Nrf2. In agreement with previously reported data from our laboratory, demonstrating the beneficial effects of HD against PD [ 27 ], we wanted to evaluate the effect of HD treatment on the activation of Nrf2 and consecutively on HO-1, Hsp-70 and Sirt-1 expression. Western blot analysis revealed a significant increase in Nrf2 in rotenone-treated mice.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Vitagenes encode for the Hsps, HO-1 and sirtuin protein systems, whose activation is most likely dependent on Nrf2. In agreement with previously reported data from our laboratory, demonstrating the beneficial effects of HD against PD [ 27 ], we wanted to evaluate the effect of HD treatment on the activation of Nrf2 and consecutively on HO-1, Hsp-70 and Sirt-1 expression. Western blot analysis revealed a significant increase in Nrf2 in rotenone-treated mice.…”
Section: Resultsmentioning
confidence: 68%
“…Further research has shown that HT administration has been able to counteract the dysregulation of the signaling mechanisms in hippocampal neurons [ 24 , 25 , 26 ]. Recently, increasing evidence reports that HT and its derivates activate the phase 2 response, leading to the expression of the nuclear factor erythroid 2-related factor (Nrf2) antioxidant pathway [ 27 , 28 ]. Interestingly, Nrf2 represents a crucial mechanism of resistance to oxidative stress and inflammation in vitro and in vivo [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is the polyphenols in these diets that are associated with the greatest reduction in neurodegeneration. Dietary polyphenols (see Figure 4 ) have multiple targets, including the inflammatory pathway, ROS, and alterations in proteostasis in disease states associated with amyloid dysfunction [ 93 ]. This could likely make them valuable in possible prevention strategies.…”
Section: Mechanisms Of Neuroprotectionmentioning
confidence: 99%
“…The daily intake of large quantities of fruit and vegetables, in addition to caloric restriction and regular exercise, is the basis of a healthy lifestyle and prevention of various chronic health problems. The high intake of phytonutrients (in particular, vitamins and plant phenols) can contribute to the reduction of the risk of various metabolic pathologies, including diabetes and related complications [ 18 , 19 ]. In this regard, there is a rich literature disclosing the benefits derived from the dietary consumption of tropical or subtropical fruits (such as mango, papaya, guava, and persimmon) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%